ESTIMASI LAJU PERTUMBUHAN PENDUDUK DI KABUPATEN JEPARA DENGAN PENDEKATAN REGRESI LINIER BERGANDA - Hetta Rachma; Mutiatun Nafisah; Nurtriana Hidayati (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
One of the main factors in planning the development of a region is the change in population. A rapid population growth rate can have adverse effects, such as poverty, unemployment, and a decrease in the quality of human resources. The purpose of this study is to predict the population growth rate in Jepara Regency by applying the multiple linear regression method, which can be used as a basis for the government in planning strategies to improve the economy, infrastructure, and other sectors, so that in the end it can have an impact on improving the welfare and quality of life of the community. The data used was obtained from BPS Jepara Regency for the period 2019-2023. Multiple linear regression analysis was applied as the method, with the number of males (X1) and females (X2) as independent variables, and the total population (Y) as the dependent variable. Based on the analysis, the predicted population in 2024 is 1,264,598 people, the same number as in 2023, indicating a stagnant growth condition. The results of this study provide important implications for government policy planning, especially in infrastructure development strategies, economic improvement, and human resource processing. The multiple linear regression method is effective in providing an accurate estimation picture, and can be the basis for future decision-making.